Apakah Spiritualitas dan Religiusitas Berperan dalam Perspektif Islam? (Do Spiritually and Religiosity Have a Role in Islamic Perspective?) - Yunizar Yunizar; Fajar Ario Wicaksono (UPT Penerbitan Universitas Jember, 2023)
Every organization strives to achieve optimal results in its work in order to attain pre-determined goals. In this regard, organizations require human resources with both quality and good performance. However, many employees work betond effective working hours, leading them to seek meaning in their work. This study aims to evaluate the influence of workplace spirituality and religiosity in an Islamic perspective on the performance of employees at Badan Amil Zakat Nasional or National Zakat Collection Agency (BAZNAS) of West Java Province. A total of 55 employee respondents were used in the study. Data Analysis was conducted using PLS-SEM through the SmartPLS application. The result of the study indicated that both workplace spirituality and religiosity in an Islamic perspective have a significant positive impact on the performance of employees both partially and simultaneously.